Erythrocyte shapes and peroxidation during high altitude adaptation on Tien-Shan-Pamir Region - Hodjamberdiev, I. B.; Kucherbaev, A.A. (Acta Andina, 2025)
lmmigrants (adults) and aborigens (adults, new-borns, children) of several Tien-Shan-Pamir zones have been studied. Stomatocytes and degenerative forms are incresed 2-3-fold in immigrants of the Internal Tien-Shan zone, with a simultaneous peroxide stimulation in erythrocyte membranes.